STRATEGI PENERJEMAHAN METAFORA KONSEPTUAL TENTANG CINTA DALAM LIRIK LAGU LANA DEL REY - Andini Arditya Sasmi, Dwi; Yunita, Tria; Rahma Fitzgelard, Arsyita; Kusumastuti, Fenty (Universitas Hamzanwadi, 2024)
This research discusses strategies for translating conceptual metaphors contained in Lana Del Rey's song lyrics. The aim of this research is to describe and analyze the translation strategies of conceptual metaphors contained in Lana Del Rey's song lyrics. This research uses qualitative methods with descriptive form. The data in this research are Lana Del Rey's song lyrics which contain conceptual metaphors about love. The data sources in this research are several Lana Del Rey songs. The data collection method in this research uses the lobservation method with note-taking techniques. This research uses data analysis methods by identifying and analyzing the meaning of conceptual metaphors about love contained in song lyrics based on Larson's theory about metaphor translation strategies and appropriate translations. The research results show that the use of translation strategies for conceptual metaphors about love in Lana Del Rey's songs is divided into three types, including (1) Translating metaphors from the source language into similes by adding the words